Active-site protein dynamics and solvent accessibility in native Achromobacter cycloclastes copper nitrite reductase. (2017) - Sen, Kakali; Horrell, Sam; Kekilli, Demet; Yong, Chin W.; Keal, Thomas W.; Atakisi, Hakan
No abstract available